2023
DOI: 10.1021/acs.biomac.3c00558
|View full text |Cite
|
Sign up to set email alerts
|

Bio-based Low-k Polymers at High Frequency Derived from Anethole: Synthesis and the Relationship between the Structures and the Properties

Fengping Liu,
Minghui Li,
Jing Sun
et al.

Abstract: Bio-based polymers have been widely investigated as sustainable low dielectric (low-k) materials in past decades. Nevertheless, a few of the polymers with excellent comprehensive properties have been achieved to satisfy the requirements of highfrequency communication application. In this paper, two fluorinated monomers (BCB-F and 2BCB-F) have been designed and successfully prepared from biomass anethole. The thermal-cross-linkable benzocyclobutene and polyfluorobenzene groups were introduced in order to obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…The catalyst 4-dimethylaminopyridine (DMAP) facilitates the reaction between epoxy and the active ester, resulting in the opening of the ring to produce ether and ester without generating hydroxyl groups. , This reaction pathway is highly advantageous for developing materials exhibiting excellent dielectric properties and low hygroscopicity, despite research on the interaction between active ester and epoxy dating back to 1988–1994 by Nishikubo et al, with limited subsequent studies on the matter. With the rapid advancement of communication technology and related fields, the pursuit of electronic devices capable of faster signal transmission and higher frequencies necessitates materials with improved dielectric properties, including low dielectric constant, low dielectric loss, and adequate stability. ,, Active esters are gaining attention as potential hardeners, leading to several studies exploring their advantages. , …”
Section: Introductionmentioning
confidence: 99%
“…The catalyst 4-dimethylaminopyridine (DMAP) facilitates the reaction between epoxy and the active ester, resulting in the opening of the ring to produce ether and ester without generating hydroxyl groups. , This reaction pathway is highly advantageous for developing materials exhibiting excellent dielectric properties and low hygroscopicity, despite research on the interaction between active ester and epoxy dating back to 1988–1994 by Nishikubo et al, with limited subsequent studies on the matter. With the rapid advancement of communication technology and related fields, the pursuit of electronic devices capable of faster signal transmission and higher frequencies necessitates materials with improved dielectric properties, including low dielectric constant, low dielectric loss, and adequate stability. ,, Active esters are gaining attention as potential hardeners, leading to several studies exploring their advantages. , …”
Section: Introductionmentioning
confidence: 99%
“…250 degC). [22][23][24][25][26][27] It is well-established that the introduction of substituents onto the four-membered ring of BCB can substantially reduce the activation energy barrier for ring-opening reactions, consequently lowering the ring-opening temperature (as indicated by the peak temperature of DSC curves). Previously, Chino et al have reported several BCB monomers with the ring-opening temperatures [?]…”
Section: Introductionmentioning
confidence: 99%